RETRACTED: Azolla of poultry farms, reproduction, production of its biomass'use as additional feed - Yoldashev Kopalboy; Tajiev Zakirjon; Buriyev Sulaymon; Razzakov Hero; Ulug'bekova Diora; Sharopova Shaxnoza (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001